Control de calidad y su relación con el proceso de extracción de aceite rojo de palma africana de la empresa Oleorios S.A., cantón Quevedo, año 2014 - Manobanda Nacif, Catalina Isabel (2015)
OLEORIOS S.A, was created and registered on August 3, 2001, for the purpose of serving the oil palm area Quevedo and its surroundings. It is a company dedicated to the purchase of oil palm fresh fruit in order to extract oil and walnut same, then market these products. This research was conducted to analyze the Quality Control and their relationship in the process of extracting red palm oil in the company "OLEORIOS SA" de Quevedo this year. For this reason it was essential to examine the current situation of the area of the production process of the company, as also the staff that takes care of it. The research contains documentary information by which knowledge of quality control and the extraction process and the rules to be applied in these processes is extracted. To obtain information several questions, with which it was obtained as a result the company OLEORIOS SA, has a laboratory where tests of samples from different stages of extraction of red palm oil are performed were developed, such as the desfrutamiento, where a sample is taken of the spine, pressing where a sample of fiber, which is from where the nut and clarifying where the oil is analyzed to indicate the amount of oily sludge, oily water is taken and oil, estimating the most important analysis performed during shipment of the product to different industries such as Pronaca, the Manufacturing to verify impurity, acidity and moisture of the product. Emphasizing that the quality control department is essential within the company as well as the staff and equipment required for the same. However, the personnel performing the….